The Perception On Ulum Al-Quran Course: A Comparative Study Betweeen Research Universities - Ibrahim, MA; Yusoff, ZHM; Yusoff, AM; Shaker, MH; Sulaiman, S; Razli, NS (Int Organization Center Acad Research, 2024)
The study of Ulum Al-Quran explores the unique of style and arrangement of the Al-Quran and the various ways in which people have tried to understand its meanings comprehensively. For Islamic studies amongst public research universities, they will need to study this course in order to complete their studies' credit hour to fulfil the requirement of their respective faculty. Hence, this study focused on students' perception of Ulum Al-Quran course in higher education at two research universities namely; National University of Malaysia (UKM) and University of Malaya (UM). The aims of this research are to know the perception of students about Ulum Al-Quran course, the acceptance of Ulum Al-Quran course outline and Ulum Al-Quran reference book or syllabus. The results from the respondents' feedbacks, is expected to assist the public research universities and the lecturers; especially the department of Islamic Studies, to assess the strengths and weaknesses of what has been done in implementing the lesson towards better improvement in Ulum Al-Quran studies.